Transição profissional para docência universitária: um estudo sobre a influência dos valores pessoais e âncoras de carreira - Pereira, Luciana de Magalhães (2016)
It is becoming increasingly natural that professionals make transitions in their careers, so, change in the nature of work, the assignments, activities and responsibilities that constitute a change of identity. The transition is the time through which the individual is changing the settings of his work, is coming out of an activity towards another with different characteristics and requirements; when there is a change, which can be deep or not in the professional paper. The present study aims to analyze the reasons for the career transition to university teaching, the career anchors and more prevalent motivational types in the researched public. A literature review was conducted to identify the key concepts of career, types of career, transition, personal values, challenges and opportunities of university teaching. This feature research is exploratory and the type is a case study with business professors in a higher education institution in the city of São Paulo. The instruments used are: Questionnaire to identify personal and professional profile, as well as reasons for the transition to university teaching career; questionnaire to identify the career anchor and the motivational type of each participant. The data analysis is qualitative and quantitative. The results indicate that the main reasons for the transition were found the opportunity rise and "old dream". The career anchor more present is Service and Dedication to a Cause and the motivational type Universalism. It is found at the end of the work that the results coincide with the characteristics of career transition particularities and characteristics inherent to university teaching, studied in this work